Transcranial Magnetic Stimulation and Aphasia Rehabilitation - Naeser, Margaret A. (2012)
Repetitive transcranial magnetic stimulation (rTMS) has been reported to improve naming in chronic stroke patients with nonfluent aphasia since 2005. In Part 1, we review the rationale for applying slow, 1 Hz, rTMS to the undamaged right hemisphere in chronic nonfluent aphasia patients following a left hemisphere stroke; and present a TMS protocol used with these patients that is associated with long-term, improved naming post- TMS. In Part, 2 we present results from a case study with chronic nonfluent aphasia where TMS treatments were followed immediately by speech therapy (constraint-induced language therapy). In Part 3, some possible mechanisms associated with improvement following a series of TMS treatments in stroke patients with aphasia are discussed.